Characteristics of injection molded parts with the areas of weld lines - Bociąga, Elżbieta; Skoneczny, Władysław (Polimery, 2020)
The weld lines in injection molded parts arise as a result of the collision of two fronts of the flowing material, which fills the mold cavity and are sometimes unavoidable. They decrease the mechanical properties and surface state of the moldings, due to insufficient connection of the fronts of melted polymer streams. The paper discusses the reasons for the occurrence of weld lines in molded parts, which have been divided into ones related to the design of the injection molded part, properties of the injected material, injection mold construction and injection parameters. The design of the molded parts should ensure even, smooth flow of the material in the cavity, but in the case of parts with many injection points, holes, varied wall thickness, complicated and irregular structure the weld lines can not be avoided. The type of material processed significantly influences the strength of the weld line area. Too high viscosity of the material, fillers and large particles of the coloring agent highly oriented in the weld line area, are the factors lowering properties of the molded part. Considering the design of the injection mold, the most important aspects in forming proper parts with weld lines are correct venting of the mold, small differences in the material temperature in all cavity areas, correctly selected injection points, avoiding jet filling of the cavity. The quality of such parts can be improved by changing the injection conditions, mainly by increasing the mold and melt temperature, also increasing the holding pressure and the injection speed. The possibilities of preventing the weld lines creation or reducing the negative effects of their occurrence have been presented, e.g. by changing the design and location of gates in injection molds, changing processing conditions or using unconventional methods of injection molding, like cascade cavity filling, push-pull and multiple live-feed injection molding, vibration process. Further examinations in the range of cyclic heating/cooling of the injection mold are suggested as the most promising regarding the quality of parts in the area of weld line, their strength and surface state.